Role of financial and non-financial incentives on employee’s performance: A study on the banking and insurance sectors of Nepal (Journal of Innovation in Academia, 2025)
This research aims to explore the impact of financial and non-financial incentives on the performance of employees working in the Nepalese banking and insurance sectors. A structured questionnaire was employed to collect the data for the study from 400 sample employees of these sectors by using a non-probability sampling method. The study found a positive correlation between financial incentives (bonuses and fringe benefits) and employee performance. By the value of Ordinal Logistic Regression, factors like age, experience, and job security did not indicate a significant impact on employee performance. In contrast to that, factors like age, experience, and job security did not indicate a significant impact on employee’s performance. The findings of the study also challenge the theoretical assumption that higher pay directly leads to improved performance, suggesting that high pay expectations might lead to performance pressure and reduced employee performance.